Vibhatsa Rasa in Fitzgerald’s The Great Gatsby - Regmi, Dipendra Raj (Kanya Journal, 2024)
This paper explores disgusting emotions as vibhatsa rasa in F. Scott Fitzgerald’s literary masterpiece The Great Gatsby (1925) through rasa theory. In this novel, Fitzgerald depicts the real picture of 1920s American society and how Americans ran after materialism. They felt that the ultimate happiness was possible through material prosperity, which is almost the same today. They work hard, earn money, get a comfortable life, and live in prosperity but lack happiness. The waves of materialism in them disturb the minds and bodies of the Americans. They are eternally blind and demonstrate moral decency while chasing their dream. Therefore, this paper examines the different kinds of disgusting emotions present in American people by observing the attitudes and feelings of the characters and their behaviors in the novel. As a qualitative applied research, the paper draws on the principles of rasa, especially vibhatsa rasa to explore disgusting emotions in the text. Physical, moral, and psychological disgust evoke the feelings of vibhatsa rasa in the text. It begins with the rise of materialism and the popularity of the American Dream. In a real sense, the deaths of Myrtle, Gatsby, and George reflect physical disgust arousing visceral emotions. The moral and psychological disgust of the characters contributes a lot to the formation of vibhatsa rasa. The series of undesirable emotions destroy the thread of human relationships. Americans need to overcome the unpleasant feelings of depression, dissatisfaction, and self-pity to imagine a better future for mankind.